Implementation of Constructivist-Metacognitive Learning Based on Character Education on Student's Metacognitive Ability - Nurhidayah Nurhidayah (Institut Agama Islam Negeri (IAIN) Salatiga, 2022)
This study aims to determine how much influence the implementation of constructivist-metacognitive learning based on character education has on students' metacognitive abilities in mathematics. The research approach carried out in this study is quasi-experimental, where the population in this study is class VII students of SMP Negeri 5 Wonomulyo, by taking simple random sampling samples obtained in this study are students of class VII A as the experimental class and class VII B as control class. The instrument used in carrying out the research is a student's metacognitive ability test. The metacognitive ability data obtained were analyzed using descriptive and inferential analysis, descriptive analysis showed that the students' metacognitive ability data were in the high category, while the results of the inferential analysis for the prerequisite test were obtained that the data were normally distributed and homogeneous, then continued with independent sample t-data analysis. The test shows that the average metacognitive ability of students with the application of constructivist metacognitive learning based on character education is greater than the average metacognitive ability of students without the application of constructivist-metacognitive learning based on character education. So it can be concluded that the application of constructivist-metacognitive learning in mathematics learning is effective in improving students' metacognitive abilities.